Identification and Comparison of Phenolic Compounds in the Preparation of Oolong Tea Manufactured by Semifermentation and Drying Processes - Dou, Jianpeng; Lee, Viola S. Y; Tzen, Jason T. C; Lee, Maw-Rong (Journal of agricultural and food chemistry, 2007)
Oolong tea manufactured via a semifermentation process possesses a taste and color somewhere between green and black teas. Alteration of constituents, particularly phenolic compounds, in the infusion of oolong tea resulting from its manufacture, was analyzed by high-performance liquid chromatography coupled to electrospray ionization tandem mass spectrometry. The identified constituents contained 2 alkaloids, 11 flavan-3-ols, 8 organic acids and esters, 11 proanthocyanidin dimers, 3 theaflavins, and 22 flavonoid glycosides, including 6 novel acylated flavonol glycosides. The tentative structures of these 6 novel compounds were depicted according to their mass fragmentation patterns in MS n (n = 1−4). In comparison with caffeine as an internal standard, relative contents of the constituents in the infusions of fresh tea shoot and different oolong tea preparations were examined. Approximately, 30% catechins and 20% proanthocyanidins were oxidized during the manufacture of oolong tea from fresh tea shoots, and 20% of total flavonoids were decomposed in a follow-up drying process. Gallocatechin-3-O-gallate and theaflavins putatively produced in the semifermentation process of oolong tea were not detected in fresh tea shoots, and the majority of theaflavins were presumably transformed into thearubigins after drying. Keywords: Catechins; flavonoid; mass spectrometry; oolong tea; theaflavin